2013
DOI: 10.1016/j.coviro.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 reverse transcriptase and antiviral drug resistance. Part 1

Abstract: HIV-1 reverse transcriptase (RT) contributes to the development of resistance to all anti-AIDS drugs by introducing mutations into the viral genome. At the molecular level, mutations in RT result in resistance to RT inhibitors. Eight nucleoside/nucleotide analogs (NRTIs) and five non-nucleoside inhibitors (NNRTIs) are approved HIV-1 drugs. Structures of RT have been determined in complexes with substrates and/or inhibitors, and the structures have revealed different conformational and functional states of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
139
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 31 publications
1
139
0
1
Order By: Relevance
“…When the polymerase adds a dinucleotide monophosphate (dNMP) to the 3= end of the primer strand, inorganic pyrophosphate (PP i ) is released. Immediately after incorporation of a nucleotide, the 3= end of the primer ϩ1 strand temporarily resides in the N site; translocation moves the end of the primer from the N site to the P site, which allows the cycle to be repeated (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…When the polymerase adds a dinucleotide monophosphate (dNMP) to the 3= end of the primer strand, inorganic pyrophosphate (PP i ) is released. Immediately after incorporation of a nucleotide, the 3= end of the primer ϩ1 strand temporarily resides in the N site; translocation moves the end of the primer from the N site to the P site, which allows the cycle to be repeated (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Structural and modeling studies have shown that the T215Y mutation is one of two (with K70R) primary AZT resistance mutations (2)(3)(4)(5). AZT-resistant HIV-1 RT transfers the AZTMP from the end of the DNA primer to the ␥-phosphate of the ATP, forming a dinucleoside tetraphosphate and producing a free 3=-OH group at the end of the primer strand (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance-associated mutations (RAMs) within or near the non-nucleoside binding pocket reduce the potency of first generation NNRTIs such as efavirenz. 9 Rilpivirine represents a new class of flexible diarylpyrimidne (DAPY) inhibitors that maintains activity against several RT resistant variants with K103N, Y181C, Y188L, and L100I mutations. 11−13 As more combination treatments such as Complera 14 include rilpivirine in antiretroviral regimens, less frequent variants of RT may emerge that contain mutations at the K101 position.…”
mentioning
confidence: 99%